2000
DOI: 10.1515/cclm.2000.023
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Lipoproteins and Endothelium

Abstract: Endothelium is an early target of pro-atherosclerotic events, which may result in functional and morphological perturbations. Oxidized low density lipoproteins, an atherogenic factor with strong cytotoxicity, may potentially contribute to altered endothelial function through the activation of a stress response, which would rescue cells to full vitality, or, conversely, by leading to cell death. Evidence is presented here for the ability of chemically oxidized low density lipoproteins to induce the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In fact covalent alterations of LDL by acetylation, oxidation or glycation, increase lipoprotein uptake and cholesterol deposition within cultured cells. Moreover oxidized or glycated LDL induce lipid peroxidation in cultured cells [Colaco and Roser, 1994;Pirillo et al, 2000;Salvayre et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact covalent alterations of LDL by acetylation, oxidation or glycation, increase lipoprotein uptake and cholesterol deposition within cultured cells. Moreover oxidized or glycated LDL induce lipid peroxidation in cultured cells [Colaco and Roser, 1994;Pirillo et al, 2000;Salvayre et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of functions and oxidative damages, induced by interactions with oxidized or glycated LDL on vascular endothelial cell, represent the early stages of the development of atherogenesis [Colaco and Roser, 1994;Khan et al, 1995;Pirillo et al, 2000;Salvayre et al, 2002].…”
mentioning
confidence: 99%
“…Unlike members of the 60 kDa family, which have been identified as the culprit autoantigens in the development of early atherosclerosis, to date there is little evidence that other hsps, including hsp70 can induce atherosclerosis. [21] It seems that overexpression of hsp70 at the site of vessel injury and atherosclerotic lesion [30,31,33,34,36] has a cytoprotective role. [46,47] This is supported by the findings of Zhu et al [48] who demonstrated that human endothelial cells express hsp70 in response to oxidized LDL only when they proliferate, thus increasing the chance of survival of rapidly proliferating cells in the lesionprone areas.…”
Section: Discussionmentioning
confidence: 99%
“…[29] The role of immunity against hsp70 in atherosclerosis is less evaluated, although many studies demonstrated that hsp70 expression is higher at sites of atherosclerotic lesions than in normal tissue, [30][31][32][33] which can be at least in part the consequence of different stressful stimuli to the vessel wall. Pirillo et al [34] found that oxidized low-density lipoprotein (LDL) induce the synthesis of hsp70 in cultured human endothelial cells, while Xu et al [35] demonstrated hsp70 expression of vascular smooth muscle cells in response to nitric oxide. Balloon angioplasty and tobacco smoking was also shown to induce hsp70 expression in human blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly accepted that modified LDLs are important for early atherosclerosis initiation and progression (39,43). Endothelial dysfunction is often considered as one of the early predominant stages in atherosclerosis development (13).…”
mentioning
confidence: 99%